2014
DOI: 10.7314/apjcp.2014.15.9.4071
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between CYP1A1 Polymorphisms and Risk of Bladder Cancer: a Meta-analysis

Abstract: Background: The effects of CYP1A1 gene polymorphisms on the risk of bladder cancer (BC) remain controversial. We carried out a meta-analysis to clarify the role of CYP1A1 gene polymorphisms in BC. Material and Methods: A comprehensive literature search was conducted up to November 20, 2013. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to estimate the strength of the association. Meta-regression, subgroup analysis, sensitivity analysis and publication bias were also performed. Results: Eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…However, most of these studies have observed no significant association with BC risk [44]. Among them, a few evaluated the association between the rs4646903 locus and BC risk and found slight trends toward association in German, Chinese, and North Indian populations [39, 40, 43, 44]. Despite the weak impact of the separate CYP SNPs (rs4646903 and rs1048943) in the present study, the combined genotype has a significant linkage with UBC ( P = 0.003).…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these studies have observed no significant association with BC risk [44]. Among them, a few evaluated the association between the rs4646903 locus and BC risk and found slight trends toward association in German, Chinese, and North Indian populations [39, 40, 43, 44]. Despite the weak impact of the separate CYP SNPs (rs4646903 and rs1048943) in the present study, the combined genotype has a significant linkage with UBC ( P = 0.003).…”
Section: Discussionmentioning
confidence: 99%
“…For example, meta-analysis of six studies found that the CYP2E1 RsaI/PstI polymorphism was associated with bladder cancer risk, especially in Caucasians [208]. Recently, meta-analysis (1059 bladder cancer cases and 1061 controls) was performed to assess CYP1A1*2B A/G (I1e462Val) and CYP1A1*2A T/C (MspI) polymorphisms in bladder cancer susceptibility [209]. Unfortunately, no association was found.…”
Section: Urinary Bladder Cancermentioning
confidence: 99%
“…However, a meta-analysis has indicated that the CY-P1A1 gene c.*1189C > T polymorphism is not associated with bladder cancer risk in Chinese, Turkish, or French populations. [10] The effects of CYP1A1 gene polymorphisms on the risk of bladder cancer remain controversial in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis revealed that the c.*1189C > T polymorphism is not associated with bladder cancer risk in Chinese, Turkish, and French populations. [10] However, several studies have indicated that the CYP1A1 gene might be strongly correlated with an increased risk of bladder cancer in populations of China and North India. [11,12] Phase II enzymes (epoxide hydrolase, glutathione S-transferase, sulfotransferase, glucuronosyltransferase) conjugate with glutathione and glucuronides to produce excretable hydrophilic products, which results in the detoxification of primary metabolites.…”
Section: Introductionmentioning
confidence: 99%